Revenue Sharing dan Profit and Loss Sharing Pada Produk Pembiayaan Lembaga Keuangan Syariah (LKS) - Intansari, Anggita Isty (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
This paper is motivated by the development of the world of sharia-based financial institutions based on Indonesia which began to develop in the nineties namely ( 1992) such as Islamic banking. Islamic financial institutions provide solutions in responding to problems in Conventional Financial Institutions, the distribution of profit calculations in the interest system creates injustice for one party because in the additional distribution of capital provided in accordance with the period of time in accordance with the percentage of interest that has been determined during the financing agreement . Otherwise, Revenue Sharing and Profit and Loss Sharing pay attention to the business partners whether they get profits or suffer losses, the additional profit sharing in this system is greatly influenced by the circumstances that occur in the business partners. Islamic Financial Institutions know the work system / circa. Profit sharing offered in sharia contract financing both with Revenue Sharing or Profit and Loss Sharing is to use the Mudharobah or Musyarokah system in accordance with the capital participation of the parties, if in the whole capital business is provided by Islamic financial institutions / one of the parties, then this condition uses the contract mudharobah, on the other hand if both of them contribute to the capital in a business / collaboration, they will use the musyarokah contract.